Sirtuins: from metabolic regulation to brain aging - Duan, Wenzhen (Frontiers in Aging Neuroscience, 2013)
Brain aging is characterized by progressive loss of neurophysiological functions that is often accompanied by age-associated neurodegeneration. Calorie restriction has been linked to extension of lifespan and reduction of the risk of neurodegenerative diseases in experimental model systems. Several signaling pathways have been indicated to underlie the beneficial effects of calorie restriction, among which the sirtuin family has been suggested to play a central role. In mammals, it has been established that sirtuins regulate physiological responses to metabolism and stress, two key factors that affect the process of aging. Sirtuins represent a promising new class of conserved deacetylases that play an important role in regulating metabolism and aging. This review focuses on current understanding of the relation between metabolic pathways involving sirtuins and the brain aging process, with focus on SIRT1 and SIRT3. Identification of therapeutic agents capable of modulating the expression and/or activity of sirtuins is expected to provide promising strategies for ameliorating neurodegeneration. Future investigations regarding the concerted interplay of the different sirtuins will help us understand more about the aging process, and potentially lead to the development of therapeutic approaches for the treatment of age-related neurodegenerative diseases and promotion of successful aging.